(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This text seeks to reflect on the actions of the Arts Pedagogical Residency, designed during the Emergency Remote Education (ERE) adopted by the Federal University of Minas Gerais. We recorded and analyzed actions that are necessary for continuity in the academic training of arts professionals. These experiences reveal how fruitful it can be to think that Digital Technologies can be in favor of the process of artistic creation and help us to keep the artistic flame burning in each of those involved in the process. We realized that it was possible to recreate other ways of exercising teacher training in Art, such as pedagogical mediation, dealing with the (im)possible.